APPLICATION OF AUGMENTED REALITY IN LEARNING THE CIRCULATORY SYSTEM: SYSTEMATIC LITERATURE REVIEW - Yaumi Yaumi; Miftahur Rohmah (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2024)
The circulatory system is one of the topics in Biology that is difficult to understand. The learning method of reading and explaining is one of the reasons it is difficult to learn Biology material and is no longer suitable to be applied in the current era. This method seems monotonous, less interesting and boring because it does not actively involve students. Student activities only read learning books and listen to teacher explanations. Augmented Reality can be used as a media to help learn the circulatory system. This research aims to analyze previous research regarding the application of Augmented Reality (AR) in learning the circulatory system. The research method used in the analysis is a systematic literature review. The literature used uses a qualitative approach and the type of literature research. The author conducted a literature review study by finding journals that matched keywords and then selected 15 relevant English or Indonesian journals. The data obtained will be analyzed descriptively and thematically. Based on the analysis, it can be concluded that the application of Augmented Reality (AR) has positive benefits in the application of circulatory system learning media, including making the learning process easier, increasing students' interest and motivation to learn, and making the learning process more fun and interesting.